REINFORCING AND SUSTAINING ENGLISH SKILLS OF HIGHER EDUCATION STUDENTS - Novitaningrum, Angella; Mahmawati, Diyah; Hidayat, Akhmad Nuris; Yusuf, Nur Laili; Wisnu, Wisnu (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This research aimed to reveal on how to reinforce and sustain higher education students’ English skills in Miftahul Midad Islamic Boarding School Lumajang. It used descriptive qualitative method to analyze the teaching and learning strategy and students’ expectation of English teaching and learning process. In order to collect the data, the researchers used observation and semi structure interview. Observation was carried out to investigate lecturer’s and students’ activities in the classroom, while interview was used to examine students’ expectation related to learning style in English classroom. The findings showed that; first, the lecturer tend to use traditional instruction, that is teacher-centered-approach. In this case, the lecturer used several strategies that promote active learning and students’ engagement in order to improve the effectiveness of the teacher-centered-approach such as using various instructional methods, using technology, asking questions, using small groups and giving students a choice, and second, all students expect that they would learn all English skills as well as grammar and pronunciation with their own learning styles. The students had several assumptions about the English classroom activities. For instance, applying group work to create relaxed and communicative classroom atmosphere, involving game-based-learning to make fun learning, practicing English directly outside the classroom, enganging interesting media in teaching and learning process, and learning English grammar with quick tricks. In addition, most of students believed that mastering English skills would be useful for their future